2011
DOI: 10.1371/journal.pone.0018601
|View full text |Cite
|
Sign up to set email alerts
|

The Guinea-Bissau Family of Mycobacterium tuberculosis Complex Revisited

Abstract: The Guinea-Bissau family of strains is a unique group of the Mycobacterium tuberculosis complex that, although genotypically closely related, phenotypically demonstrates considerable heterogeneity. We have investigated 414 M. tuberculosis complex strains collected in Guinea-Bissau between 1989 and 2008 in order to further characterize the Guinea-Bissau family of strains. To determine the strain lineages present in the study sample, binary outcomes of spoligotyping were compared with spoligotypes existing in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 39 publications
7
40
2
Order By: Relevance
“…The frequency of M. bovis in persons in this study (0.4%) is similar to that found in other studies of human TB in Africa ( 11 ) and South and Central America ( 12 ), but much lower than that observed among selected populations in Tanzania (16%) ( 13 ), Ethiopia (17%) ( 14 ), and Mexico (28%) ( 15 ). These findings indicate that the overall contribution of M. bovis to human TB is minor but greater in specific areas.…”
Section: Discussionsupporting
confidence: 89%
“…The frequency of M. bovis in persons in this study (0.4%) is similar to that found in other studies of human TB in Africa ( 11 ) and South and Central America ( 12 ), but much lower than that observed among selected populations in Tanzania (16%) ( 13 ), Ethiopia (17%) ( 14 ), and Mexico (28%) ( 15 ). These findings indicate that the overall contribution of M. bovis to human TB is minor but greater in specific areas.…”
Section: Discussionsupporting
confidence: 89%
“…However, three studies have reported decreasing prevalence of M. africanum (i.e. Lineage 5 and 6) in Cameroon, Guinea-Bissau and Burkina Faso [204206], supporting of the lower “virulence” of the “ancestral” lineages. Therefore, although sub-lineage differences might obscure general patterns, taken together, these studies support the view that on average “modern” MTBC lineages are more transmissible than other strains.…”
Section: The Consequences Of Genomic Diversity In Mtbcmentioning
confidence: 99%
“…Moreover, these lineages have been generally associated with the recent transmission of TB and with epidemics. This is true particularly for the Beijing family, which is ubiquitous and in the process of invading many countries, such as Vietnam (Nguyen et al, 2012), and also for the LAM family, which is spreading in Africa (Godreuil et al, 2007c;Groenheit et al, 2011).…”
Section: Mtb and The Mtbc: A History Of Hostsmentioning
confidence: 99%